Per-oral cross-facial sural nerve graft for facial reanimation - Joohee Jeong; Akram Abdo Almansoori; Hyun-Soo Park; Soo-Hwan Byun; Seung-Ki Min; Han-Wool Choung; Joo Yong Park; Sung Weon Choi; Bongju Kim; Soung-Min Kim; Jong-Ho Lee (SpringerOpen, 2018)
Abstract Background Cross-facial nerve graft is considered the treatment of choice for facial reanimation in patients with unilateral facial palsy caused by central facial nerve damage. In most cases, a traditional parotidectomy skin incision is used to locate the buccal and zygomatic branches of the facial nerve. Methods In this study, cross-facial nerve graft with the sural nerve was planned for three patients with facial palsy through an intraoral approach. Results An incision was made on the buccal cheek mucosa, and the dissection was performed to locate the buccal branch of the facial nerve. The parotid papillae and parotid duct were used as anatomic landmarks to locate the buccal branch. Conclusions The intraoral approach is more advantageous than the conventional extraoral approach because of clear anatomic marker (parotid papilla), invisible postoperative scar, reduced tissue damage from dissection, and reduced operating time.